Analisis Soal Tes Sumatif Bahasa Indonesia Kelas V MI di Sukoharjo Tahun 2025 - Resya Zuhra Namira; Suprapti (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the quality of summative Indonesian language test questions for grade V MI in Sukoharjo in 2025 based on their suitability with Learning Outcomes, Learning Objectives, and cognitive levels of the revised Bloom's Taxonomy. The study used a qualitative approach with a library method on 50 questions through documentation techniques and descriptive content analysis. The results showed that all questions were in accordance with Learning Outcomes and Learning Objectives, but the coverage of the material was not evenly distributed because there were still 15 Learning Objectives and 1 material that had not been tested and the dominance of reading and listening elements. From the cognitive aspect, the questions were dominated by level C2 (MOTS) and did not cover level C5, so that students' higher-order thinking skills (HOTS) had not developed optimally. This study is limited to the analysis of summative Indonesian language test questions for grade V MI in Sukoharjo in 2025, which includes compliance with Learning Outcomes and Learning Objectives, and the cognitive domain of the Revised Bloom's Taxonomy (C1–C6) in written questions, without examining the learning process, student learning outcomes, or the affective and psychomotor domains. This study recommends that teachers compile questions more proportionally according to all Learning Objectives and increase the variety of questions at the HOTS level so that learning evaluation is more comprehensive.